How to Advance Sustainable Innovations for Circular Bioeconomy: Perspectives from a Public Research Institute - Tapiola, Titta; Leppälä, Jarkko; Ghalibaf, Maryam (Faculdade de Engenharia da Universidade do Porto, 2024)
This article presents a case study of public research institute innovation process for the circular bioeconomy in Finland. If an invention is to become an innovation, it requires actor alignment and cooperation from research to product development all the way to the end user. Despite the high uncertainty, the decision makers along the value chain need to identify possible directions and promising options, in addition to managing various risks. Support for these decisions is crucial to enable sustainable innovations. Furthermore, the role of public research institutions in providing “seeds” for innovations has been researched less extensively than the role of private companies or universities. This paper develops and tests a new circular bioeconomy product questionnaire to assist researchers. The questionnaire was designed for Natural Resources Institute Finland, combining risk management, new product development, and innovation process perspectives. The authors interviewed researchers and developed the framework further based on the interview analysis and tested it in a workshop. For the end product to succeed, it is necessary to understand the requirements of the entire value chain, especially the needs of end users. The research (and innovation) process should already involve stakeholders in the early stages to better meet their expectations.
Keywords: inventions; innovations; enhanced innovation process; public research institute; public sector innovation; bioeconomy; circular economy; circular bioeconomy